New tools for learning - Dickinson, Dee (The Turkish Journal of Pediatrics, 1999)
In the last twenty-five years more has been learned about the human brain than in the past history of mankind. Through the use of new technologies such as PET and CAT scans and functional MRI's, it is now possible to see and learn much about the human brain while it is in the process of thinking. The research of neuroscientists, such as Marian Diamond, has demonstrated that the brain changes physiologically as a result of learning and experience —for better or worse — and that plasticity can continue throughout the lifespan. It appears that there are particular kinds of environments that are most conducive to the development of good mental equipment. They are positive, nurtlring, stimulating, and encourage action and interaction. Many of the most effective schools and training programs have created such high-challenge low-threat environments.It is also very clear that intelligence is not a static structure, but an open, dynamic system that can continue to develop throughout life. This understanding is being utilized not only in school systems but in the workplace, where training programs show that even at the adult level people are able to develop their intelligence more fully. Corporations such as Motorola have implemented programs in which they are training their employees, managers, and executives to think, problem-solve and create more effectively using strategies developed by such educational innovators as Reuven Feurstein, J.P. Guilford, and Edward de Bono.A most recent development is in the new kinds of technology that make it possible for people to take responsibility for their own learning as they access and process information through the internet, communicate with experts anywhere in the world, and use software that facilitates higher order thinking and problem-solving. Computers are in no way replacing teachers, but rather these new tools allow them to spend more time being facilitators, mentors, and guides. As a result, teachers and students are able more often to collaborate on creating new knowledge as well as mastering the basics.As technology becomes more ubiquitous, there is growing recognition of the importance of the arts in humanizing the curriculum. "More high-tech, more need for high-touch" is becoming the by-word of many schools. They recognize that the arts are not only culturally important and civilizing influences, but they can facilitate the learning of almost any subject.I believe that these four concepts — the plasticity of the brain, the modifiability of intelligence, the use of technology as a powerful new tool for learning, and the renaissance of the arts in education — have major implications specifically for educational systems and generally for the future of our world. In this time of rapid change, leading-edge educational systems are equipping people with the ability to learn, unlearn, and relearn continually. They are giving students meaningful opportunities to apply what they have learned in order to turn information into knowledge. And - of critical importance if any of this is to lead to a healthy future — they are helping students to learn to use knowledge responsibly, ethically, and with integrity. Furthermore, they are involving students in experiences that develop compassion and altruism in the process of their education. Our complex world urgently needs more people who have developed their fullest potential in mind, body, and spirit.